1998
DOI: 10.1111/j.1751-0813.1998.tb12331.x
|View full text |Cite
|
Sign up to set email alerts
|

A severity score for spontaneous canine acute pancreatitis

Abstract: Assessment of severity of spontaneous canine acute pancreatitis using pancreatic enzyme activities is potentially inaccurate. The use of a severity score based upon organ system compromise was more accurate in determining the likelihood of mortality in spontaneous canine acute pancreatitis. This is compatible with the hypothesis that severe canine acute pancreatitis is a multiple organ failure syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
2
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 6 publications
5
46
2
5
Order By: Relevance
“…Previous reports have suggested that assessing the severity of AP using pancreatic enzyme activity potentially is inaccurate. In 1 report, the use of a severity score based upon organ system compromise was more accurate in determining the likelihood of mortality in AP . The CRP concentration appeared to be associated with disease severity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous reports have suggested that assessing the severity of AP using pancreatic enzyme activity potentially is inaccurate. In 1 report, the use of a severity score based upon organ system compromise was more accurate in determining the likelihood of mortality in AP . The CRP concentration appeared to be associated with disease severity.…”
Section: Discussionmentioning
confidence: 95%
“…In 1 report, the use of a severity score based upon organ system compromise was more accurate in determining the likelihood of mortality in AP. 25 The CRP concentration appeared to be associated with disease severity. In another study, no relationship was observed between CRP concentration and outcome.…”
Section: Discussionmentioning
confidence: 97%
“…Further studies are needed to investigate the relationship between CIRCI and AP in dogs. Ruaux & Atwell (1998) proposed a system for rating the clinical severity of AP on a scale ranging from 0 to 4, indicating the number of organs other than the pancreas exhibiting signs of compromise or failure. In this system, the BUN, CRE, ALP, ALT, GLU and WBC count are used to predict prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, individual measurements of Spec cPL or fPL concentrations cannot be used to determine the severity of pancreatitis. However, severity based on histopathologic features may not reflect clinical severity in animals with pancreatitis, and accurate assessment of clinical severity of pancreatitis is challenging . The utility of serum PLI concentration in determining the clinical severity of pancreatitis in dogs and cats requires evaluation in clinical studies in association with other markers of severity and using appropriate scoring systems for clinical severity.…”
Section: Pli As a Marker Of Severity In Pancreatic Diseasementioning
confidence: 99%